Narcissism and coach interpersonal style: A self-determination theory perspective - Matosic, D.; Ntoumanis, N.; Boardley, I.; Sedikides, C.; Stewart, B.; Chatzisarantis, Nikos (2015)
Athletes’ sport experiences are often influenced by the interpersonal styles of communication used by their coaches. Research on personality antecedents of such styles is scarce. We examined the link between a well-researched personality trait, namely narcissism, and two types of coaching interpersonal style, namely autonomy-supportive and controlling styles. We also tested the mediating roles of dominance and empathic concern in explaining the relations between narcissism and the two coaching interpersonal styles. United Kingdom-based coaches (N = 211) from various sports completed a multi-section questionnaire assessing the study variables. Regression analyses revealed a positive direct relation between narcissism and controlling coach behaviors. Furthermore, empathy (but not dominance) mediated the positive and negative indirect effects of narcissism on controlling and autonomy-supported interpersonal styles, respectively. We discuss these findings in terms of their implications for coaching and the quality of athletes’ sport experiences.